Pengaruh Perdagangan International Terhadap Ekspor Dan Impor - Imelda Sahfitri; Nur Afriyanti; Nurvadila; Delsa Yolanda Putri; Nur Fitriana (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This research aims to determine the influence of international trade on Indonesia. International business is business between countries through import and export activities. The impact of imports and exports on economic growth in Indonesia is very large. This is because exports are one source of state income, and through import activities you can obtain goods that do not yet exist in the country or goods that are in limited supply to meet people's demands and needs. When the economy grows, national income increases and society becomes economically prosperous. Many studies have found that exports can generate foreign exchange which can be used to support domestic sector development and encourage economic growth. From this research we can find out what impact international trade has on Indonesia.